A systems approach to lithium-ion battery management - Weicker, Phillip (Artech House power engineering series., 2014)
Previously limited to heavy and bulky lead-acid storage batteries, large format batteries were used only where absolutely necessary as a means of energy storage. The improved energy density, cycle life, power capability, and durability of lithium ion cells has given us electric and hybrid vehicles with meaningful driving range and performance, grid-tied energy storage systems for integration of renewable energy and load leveling, backup power systems and other applications. This book discusses battery management system (BMS) technology for large format lithium-ion battery packs from a systems perspective. It covers the future of BMS; provides new ways to generate, use, and store energy; free us from the perils of non-renewable energy sources; provides a full update on BMS technology, covering software, hardware, integration, testing, and safety. --